1996
DOI: 10.1172/jci118672
|View full text |Cite
|
Sign up to set email alerts
|

A femtomolar-acting neuroprotective peptide.

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
209
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(216 citation statements)
references
References 62 publications
6
209
0
1
Order By: Relevance
“…One to 100 fM ADNF, 100 pM to 1 nM IGF-I, 1-10 nM bFGF, and 1-10 nM HNG suppressed neuronal death by A␤1-43 to the levels of basal cell death, indicating that these factors selectively abolish neurotoxicity by A␤ without affecting basally occurring death. Higher concentrations of IGF-I, bFGF, and HNG exerted complete neuroprotection, whereas Ն100 nM concentrations of ADNF lost its neuroprotective activity, as repeatedly reported in the literature (Brenneman and Gozes, 1996;Brenneman et al, 1998;Glazner et al, 1999). Although it remains unknown why the full action of ADNF was only observed at high femtomolar to low picomolar concentrations, such a phenomenon was not attributed to potential combination of its rescue action by low concentrations and its toxic action by higher concentrations, because ADNF alone was not neurotoxic, even at 100 nM (data not shown).…”
Section: Comparison Of the Action Of Hng With Those Of Adnf Igf-i Asupporting
confidence: 80%
See 2 more Smart Citations
“…One to 100 fM ADNF, 100 pM to 1 nM IGF-I, 1-10 nM bFGF, and 1-10 nM HNG suppressed neuronal death by A␤1-43 to the levels of basal cell death, indicating that these factors selectively abolish neurotoxicity by A␤ without affecting basally occurring death. Higher concentrations of IGF-I, bFGF, and HNG exerted complete neuroprotection, whereas Ն100 nM concentrations of ADNF lost its neuroprotective activity, as repeatedly reported in the literature (Brenneman and Gozes, 1996;Brenneman et al, 1998;Glazner et al, 1999). Although it remains unknown why the full action of ADNF was only observed at high femtomolar to low picomolar concentrations, such a phenomenon was not attributed to potential combination of its rescue action by low concentrations and its toxic action by higher concentrations, because ADNF alone was not neurotoxic, even at 100 nM (data not shown).…”
Section: Comparison Of the Action Of Hng With Those Of Adnf Igf-i Asupporting
confidence: 80%
“…Although each of ADNF, IGF-I, and bFGF could suppress neurotoxicity induced by A␤, as shown by previous studies (Brenneman and Gozes, 1996;Dore et al, 1997;Mark et al, 1997;Brenneman et al, 1998), ADNF, IGF-I, and bFGF only inhibited V642I-APP-induced cytotoxicity and could not affect neuronal cell death by mutant PS1 and PS2. In contrast, HN and HNG suppressed the neurotoxicities by mutants of APP, PS1, and PS2, which are all known FAD genes.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…ADNP mRNA is regulated by VIP (Bassan et al, 1999), and here we demonstrate that incubation with VIP resulted in higher levels of ADNP-like immunoreactivity in conditioned media from astrocytes. VIP is known to produce a neurotrophic milieu (Brenneman et al, 1990;Gozes et al, 1991;Waschek, 1995;Brenneman and Gozes, 1996;Gressens, 1999;Brenneman et al, 2003), and it has been suggested that ADNP constitutes part of this protective environment. However, it is unclear whether ADNP is released into the medium by a constitutive or regulated process.…”
Section: Discussionmentioning
confidence: 99%
“…Colivelin (CLN), the strongest HN derivative so far developed, is a fusion peptide composed of a potent HN derivative named AGA-(C8R)HNG17 attached to the C terminus of activitydependent neurotrophic factor (ADNF) (Brenneman and Gozes, 1996;Brenneman et al, 1998;Chiba et al, 2004Chiba et al, , 2005Chiba et al, , 2006Matsuoka et al, 2006). Our earlier studies indicated that HN and CLN suppressed AD-relevant neuronal death by activating STAT3 in vitro Hashimoto et al, 2005;Matsuoka et al, 2006).…”
Section: Introductionmentioning
confidence: 99%